Critical Reading and Writing in the 21st Century. - Kazazoğlu, Semin (Cambridge Scholars Publishing, 2022)
The art of critical thinking has its roots in the 5th century. In the beginning, it was defined as a path to intellectuality. In other words, early scholars regarded wisdom as having the capacity to judge logically. Today, its meaning has also been expanded to creativity. Hence, within critical thinking, an individual may possess both purposeful questioning and creativity. Concerning these aspects, it has become prominent in the field of education. We need to change the way we teach pupils to think to prepare them for life in the 21st century. The process of inquiry is about training our stude.